2013
DOI: 10.1371/journal.pone.0073026
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Flagella in Clostridium difficile Pathogenesis: Comparison between a Non-Epidemic and an Epidemic Strain

Abstract: Clostridium difficile is a major cause of healthcare-associated infection and inflicts a considerable financial burden on healthcare systems worldwide. Disease symptoms range from self-limiting diarrhoea to fatal pseudomembranous colitis. Whilst C. difficile has two major virulence factors, toxin A and B, it is generally accepted that other virulence components of the bacterium contribute to disease. C. difficile colonises the gut of humans and animals and hence the processes of adherence and colonisation are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

10
153
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 123 publications
(178 citation statements)
references
References 36 publications
10
153
3
Order By: Relevance
“…7C). The timing and expression of sigD and flagellar genes during infection affect colonization by and the virulence of C. difficile and other motile pathogens and thus probably contribute to the decreased virulence of the CD1492 mutant in the animal model (43)(44)(45)(46)(47).…”
Section: Deletion Of Cd1492 Results In Decreased Virulence In An Animmentioning
confidence: 99%
“…7C). The timing and expression of sigD and flagellar genes during infection affect colonization by and the virulence of C. difficile and other motile pathogens and thus probably contribute to the decreased virulence of the CD1492 mutant in the animal model (43)(44)(45)(46)(47).…”
Section: Deletion Of Cd1492 Results In Decreased Virulence In An Animmentioning
confidence: 99%
“…The spo0A gene, encoding the master regulator of sporulation (59, 60), was 2.4-fold and 2.3-fold downregulated in the logarithmic and stationary growth phases, respectively, and many other sporulation genes showed a similar effect (see Table S2 in the supplemental material). Furthermore, several genes encoding surface-associated proteins (such as slpA and 5 other paralogs of slpA) (16), flagellum-associated genes (18,61), and cd1581 (a gene with a potential effect on adhesion and intestinal colonization) (19) were significantly downregulated.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, there is a clear link between motility and toxin production, as the alternative sigma factor SigD is required for both (81). Interestingly, flagellar operon mutants showed changes in both toxin levels (82) and their capacity to adhere to Caco-2 cells (61). Finally, more general effects of stress (nutrient depletion or temperature) on toxin levels were noted (83,84).…”
Section: Discussionmentioning
confidence: 96%
“…This diversity is believed to account for the differences in motility between C. difficile 630 and R20291 [15]; Stabler et al [15] observed that C. difficile 630 was less motile than R20291. It is pertinent to note that differences in motility and number of flagella have been observed between clonal isolates of C. difficile R20291 [12,15,22]. The study of Stabler et al [15] revealed R20291 to be more motile than 630; however, research by Baban et al [12] has shown R20291 to be less motile than 630 and to have one polar flagellum, as opposed to Martin et al [22], who observed multiple flagella in the R20291 strain.…”
mentioning
confidence: 99%
“…However, the contribution of flagella to the pathogenesis of C. difficile is complex and not yet fully understood. There is increasing scientific evidence to suggest that flagella play a more direct role in virulence, via modulation of toxin expression [4,12] rather than simply providing force-driven motility towards nutrients available in the gut. In this review the importance of flagella to the pathogenicity of C. difficile is discussed.…”
mentioning
confidence: 99%